Sekcija “Indivīds un vara Baltijas kultūrtelpā”: tēžu krājums - Latvijas Universitāte. Latvijas vēstures institūts; Latvijas Universitāte. 79. zinātniskā konference (Latvijas Universitāte Latvijas vēstures intitūts, 2021)
Krājumā apkopotas 2021. gada 26. februārī Latvijas Universitātes 79. Starptautiskās zinātniskās konferences ietvaros LU Latvijas vēstures institūta organizētās sekcijas “Indivīds un vara Baltijas kultūrtelpā” nolasīto referātu tēzes. Tajās aplūkota indivīda un varas mijiedarbība sociologu un vēsturnieku skatījumā visai plašā laika diapazonā – no 13. gs. līdz 20. gs. Tēzēs ietvertās atziņas balstītas padziļinātās rakstīto avotu studijās, ietver jaunākās zinātniskās atziņas pētāmajā problemātikā un reflektē par atsevišķu faktu interpretāciju plašsaziņas līdzekļos. Konferencē nolasīti 10 referāti, autori – LU LVI un LU FSI vadošie pētnieki un pētnieki.

This volume contains the abstracts of the session “The Individual and State Power in the Baltics”, held on 26 February 2021 within the frame of the 79th International Scientific Conference of the University of Latvia by the Institute of Latvian History, University of Latvia. It examines the interaction between the individual and power in the period from the 13th to the 20th century, as viewed by sociologists and historians. The results presented in the abstracts are based on in-depth studies of written sources, incorporating the latest scientific findings relating to the research topics and reflecting on the interpretation of particular facts in the media. The authors of the 10 reports read at the conference are senior researchers and researchers from the Institute of Latvian History, University of Latvia, and the Institute of Philosophy and Sociology, University of Latvia.
Session “The Individual and State Power in the Baltics”: Abstracts
Keywords: Research Subject Categories::HUMANITIES and RELIGION; indivīds un vara; Baltijas kultūrtelpa; Latvijas vēsture